Evaluating investements in CRM with real options - Maklan, Stan; Knox, Simon; Ryals, Lynette (Cranfield University, 2004)
CRM practices are being adopted in most industry sectors to build stronger relationships with customers in order to develop superior customer value and increase shareholder value. This article questions the basis upon which the business case for CRM investments is traditionally made, highlighting the shortcomings of focusing only upon discounted cash flows, and points towards a strategic approach that accounts for such investments in asset value terms. A case study is used to illustrate how to value the returns using both cash flow and strategic investment calculations for comparative purposes. The managerial implications are discussed.